Phenetic Study on Clustered Pinanga of Java and Bali - JOKO R. WITONO (Biodiversitas Journal of Biological Diversity, 2003)
The objective of the study was to know relationships of clustered Pinanga of Java and Bali based on morphologicalcharacters. Observation was done to 115 clustered Pinanga specimens (P. coronata), 18 of which were assigned asOperational Taxonomic Units (OTUs). The morphological characters noted, analyzed using versions of the numericaltaxonomy system / NTSYS version 1.80, 1993. The phenogram presents that clustered Pinanga of Java and Bali divided into two groups (clusters): specimens from lowland forest (0-750 m asl) and specimens from montane forest (750 m asl or more). The cluster division is not dependent on the geographical distribution of the OTUs, but rather altitudes.Â© 2003 Jurusan Biologi FMIPA UNS SurakartaKey words: Java, Bali, NTSYS, OTUs, clustered Pinanga, phenetic study.